Childhood Drowning: Review of Patients Presenting to the Emergency Departments of 2 Large Tertiary Care Pediatric Hospitals Near and Distant From the Sea Coast. Issue 5 (May 2020) - Cohen, Neta; Scolnik, Dennis; Rimon, Ayelet; Balla, Uri; Glatstein, Miguel
Abstract : Objective: Drowning is a leading cause of death among infants and toddlers. Unique physiological and behavioral factors contribute to high mortality rates. Drowning incidents predominantly occur during warmer months and holidays. The aim of this study was to describe the characteristics of pediatric drowning victims who attended 2 different emergency departments (EDs), 1 near and 1 distant from the sea coast, to recognize risk factors, complications, causes of death, and the educational needs of families and caregivers. Methods: Retrospective cohort analysis of incident history, clinical presentation, treatments, and outcomes of drowning victims was performed. Data were analyzed both by age group and proximity of institution to the sea coast. Results: From 2005 to 2015, 70 drowning patients presented to the 2 institutions; there was no difference in incident history or outcomes based on proximity to the sea coast. Fifty-six percent of patients were younger than 6 years, the majority drowning in pools. More of the older children drowned in the sea (48% vs 23%). Half of all patients were treated and followed in the ED or ward, and the other half were treated in the pediatric intensive care unit; 12 suffered severe complications, including 5 diagnosed with brain death. Cardiopulmonary resuscitation was performed in 80% of the fatal group and 23% of the nonfatal group ( P = 0.006). Seven children who experienced a cardiac arrest with hypothermia were treated before arrival in the ED, and 5 had ongoing cardiac arrest upon arrival in the ED (these were the 5 suffering brain death). Discussion: Most of patients younger than 6 years drowned in swimming pools, suggesting that parents are perhaps less vigilant in these circumstances, even though they may remain in close proximity. Active adult supervision entails attention, proximity, and continuity. Educational efforts should be aimed at reminding parents of this, especially in the summer months.